Factors That Play A Role In Increasing Food And Beverage Employee Loyalty - Diva Az-Zahra Agustian; Lisa Harry Sulistiyowati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study examines how intrinsic motivation and monetary incentives affect employee loyalty in the food and beverage sector. Given the high turnover rate in the service sector, the goal of this study is to ascertain how workers’ long term commitment may be strengthened by combining material incentives with psychological reinforcement. This research employs both descriptive and associative methodologies in a quantitative manner. 100 workers were chosen using the Slovin algorithm with a 5% margin of error, and structured questionnaires were used to gather data. Using IBM SPSS version 27, multiple linear regression, traditional assumption tests, and hypothesis tests (t-test and F-test) utilized to analyze the data. The result show that employee loyalty is significantly improved by both monetary incentive and intrinsic motivation, both concurrently and partly. The F-test results (F = 74.775; sig. 0.000) confirm the simultaneous effect, according to the coefficient of determination (R2= 0.607), these two factors account for 60.7% of the variance in employee loyalty. In comparison to intrinsic motivation (t = 4.195), financial reward has a somewhat greater impact (t = 7.699). The regression model ???? = 0.133 + 0.289 (????1) + 0.335 (????2), this study demonstrates that retaining employee loyalty un the F&B industry requires a mix of monetary incentives and psychological support. The research suggests that F&B managers combine financial compensation and intrinsic motivation to optimize staff retention. This well-being and professional recognition-based strategy effectively reduces turnover costs and increases productivity, ultimately supporting service industry stability and regional economic growth. Theoretically, this study updates HR management by proving that the synergy between incentives and psychological factors is key to loyalty, going beyond previous research that focused on only one aspect.